Pengembangan Media Pembelajaran PPT Interaktif untuk Meningkatkan Pemahaman Siswa dalam Mata Pelajaran PKn di Sekolah Dasar - Revalina Hidayat; Irma Apriani; Lisa Putri; Ilham Muarif; Melsi Prima Dola; Masri Yuanda (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to review in depth various literature related to the development of interactive PowerPoint (PPT)-based learning media in order to improve students' understanding of Civic Education (PKn) subjects at the elementary school level. Innovative and interesting learning media are considered to have an important role in creating a more enjoyable, active, and meaningful learning atmosphere for students. In the literature reviewed, interactive PPT media has been proven to be able to present material visually, audibly, and interactively, thus helping students understand abstract concepts in PKn more concretely. The method used in this study is a literature review of various national and international journals, scientific articles, and relevant research reports in the last five years. The results of the study show that the use of interactive PPT not only increases the attractiveness of learning, but is also able to encourage active student participation, strengthen memory, and build a deeper understanding of national values, democracy, and social responsibility. In addition, the development of this media requires careful planning, starting from the design of the display, the preparation of content that is in accordance with the curriculum, to the integration of interactive elements such as quizzes, animations, and multimedia links. Based on findings from various literature, it can be concluded that interactive PPT media is an effective alternative that can be used by teachers to significantly improve the quality of civics learning in elementary schools.